OTOMATISASI PENERIMAAN DAN PENGIRIMAN PESAN DENGAN SISTEM TERDISTRIBUSI UNTUK MENDUKUNG PENYEBARAN INFORMASI AKADEMIK - Wangsit Setyoadi; Hero Wintolo; Yuliani Indrianingsih (Compiler, 2012)
Advances in technology are increasing rapidly, especially in the field of information and communication technology provides convenience in exchanging information. One widely used communication tool today is the mobile phones which have facilities sending messages or SMS (Short Message Service). With the mobile phone application development, application technology of short message or SMS widely used for more general purposes, one of which is in the academic field. To facilitate the exchange of academic information, including financial data, grades, and exam schedules, distributed systems into tools that are able to provide and process information dynamically.To facilitate the exchange of academic information between the school and students, they invented a system that is distributed for the dissemination of academic information that can be accessed via SMS.Academic information dissemination system based on short message or SMS can enhance the effectiveness of the dissemination of information between the school and students. With a system of information exchange is expected to be faster and more controlled because the cost for all messages can be recorded.